Victim’s Paradigm in European Union Criminal Law - Gurevičs, Dāvids (Teisė, 2023)
The victim’s legal status and participatory rights in criminal proceedings vary among the European Union member states, which can potentially hinder the harmonisation of the field of criminal law. The aim of this article is to reveal the main features that determine the victim’s paradigm in European Union criminal law by focusing on the rights which the member states are obliged to guarantee in their criminal justice systems. Considering that criminal proceedings must result in a fair balance of interests of the parties involved, this article concludes that, in the victim’s paradigm enshrined in the European Union legal acts concerning the area of criminal law, the victim must be endowed with certain procedural rights, however, for that very reason, as an actor of the criminal justice system, the victim might be required to participate in the proceedings.